Evaluation of the Implementation of the 2023 Computer-Based National Assessment Using the Cipp Model at SD Inpres Noelbaki - Naros, Gabriel; Taku Neno, Khatrin J.; Enstein, Jhon (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to evaluate the preparation, process, and challenges of implementing the 2023 Computer-Based National Assessment (ANBK) at SD Inpres Noelbaki, Kupang Regency, by using a qualitative descriptive approach with the CIPP (Context, Input, Process, Product) evaluation model. The study involved various parties, including the Headmaster, Deputy for Facilities and Infrastructure, Deputy for Curriculum, Proctor, the 5th Grade Homeroom Teacher, and 5th-grade students. Data were collected through interviews, observations, and documentation, and their validity was tested through time, technique, and source triangulation, then data analyzed by using Miles and Huberman's interactive model. The results show that technical preparation included providing equipment such as Chromebook, Wi-Fi networks, the ANBK application, and exam simulations to ensure readiness. Non-technical preparation focused on guiding students through the questions. The challenges in preparation included students' low literacy and numeracy skills, limited guidance time, internet connectivity issues, and minimum ANBK socialization. The ANBK process was conducted as scheduled on October 18-19, 2023, with 30 students participating in two sessions. The challenges faced included internet connectivity disruptions, limited student skills in using computers, and student anxiety due to insufficient literacy and understanding of the questions. The results indicated that 63.33% of students achieved the minimum competency in literacy and 30% in numeracy.This study recommends improving numeracy, socialization, guidance time, and technical support for future ANBK implementations.